Respuesta :
Answer: [A]: " (3, 10) ".
____________________________________________________
Explanation:
___________________________________________________
Since: y = 2x +4 = 3x + 1 ; Solve for "x" ;
_________________________________________
2x + 4 = 3x + 1 ;
_________________________________________
Subtract "2x" and subtract "4" from each side of the equation:
__________________________________________
2x + 4 − 2x − 4 = 3x + 1 − 2x − 4 ;
__________________________________________
to get: 0 = x − 3 ;
_________________________________________
Add "3" to both sides of the equation:
________________________________________
0 + 3 = x − 3 + 3 ;
________________________________________
to get: 3 = x ;
↔ x = 3 ;
_______________________________________
Now, let us plug "3" into "x" for one of the equations given, to solve for "y" ;
________________________________
Start with the first equation:
_______________________________________________________
y = 2x+4 ; y = (2*3) + 4 ; y = 6 + 4 ; y = 10 .
_______________________________________________________
Let us try with the second equation, to check our answer:
_______________________________________________________
y = 3x +1 ; y = (3*3) + 1 ; y = 9 + 1 ; y = 10 ; Yes!
_______________________________________________________
So, x = 3, y = 10 ; or (3, 10) ; which is: Answer choice: [A].
_______________________________________________________
____________________________________________________
Explanation:
___________________________________________________
Since: y = 2x +4 = 3x + 1 ; Solve for "x" ;
_________________________________________
2x + 4 = 3x + 1 ;
_________________________________________
Subtract "2x" and subtract "4" from each side of the equation:
__________________________________________
2x + 4 − 2x − 4 = 3x + 1 − 2x − 4 ;
__________________________________________
to get: 0 = x − 3 ;
_________________________________________
Add "3" to both sides of the equation:
________________________________________
0 + 3 = x − 3 + 3 ;
________________________________________
to get: 3 = x ;
↔ x = 3 ;
_______________________________________
Now, let us plug "3" into "x" for one of the equations given, to solve for "y" ;
________________________________
Start with the first equation:
_______________________________________________________
y = 2x+4 ; y = (2*3) + 4 ; y = 6 + 4 ; y = 10 .
_______________________________________________________
Let us try with the second equation, to check our answer:
_______________________________________________________
y = 3x +1 ; y = (3*3) + 1 ; y = 9 + 1 ; y = 10 ; Yes!
_______________________________________________________
So, x = 3, y = 10 ; or (3, 10) ; which is: Answer choice: [A].
_______________________________________________________